Company Merger: Option Or Necessity? - Rolib Sitorus; Ricky Banke; Joy Zaman Felix Saragih (CV. RADJA PUBLIKA, 2025)
This study aims to analyze corporate mergers as a business strategy—whether they are pursued as a deliberate choice or as a necessity driven by external pressures such as financial crises, intense market competition, or regulatory changes. In the era of globalization and rapid market dynamics, many companies opt to merge to strengthen their market position, improve operational efficiency, and enhance shareholder value. This research employs a qualitative method with a case study approach, focusing on several Indonesian companies that have undergone mergers in the past five years. Data were collected through in-depth interviews, document analysis, and literature review on mergers and acquisitions. The findings reveal that most mergers are driven by a combination of strategic choices and market-driven necessities. In certain cases, mergers were imperative to ensure business continuity due to poor financial performance or regulatory pressures. The study concludes that corporate mergers should not be viewed dichotomously as either a choice or a necessity, but rather as a strategic process influenced by a variety of internal and external factors.